(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
Airborne particulate matter (PM) samples collected at a semi-residential area in Dhaka during the period of 1997-2005 by Gent sample. The samples were analyzed by PIXE (Proton Induced X-Ray Emission). It was found that due to the banning of leaded gasoline together with other stepwise policy intervention, the air quality tends to become moderate. From the high standard deviation of Pb after banning of leaded gasoline, it can remarked that there is still emission of Pb which is not so frequent. As a result the yearly average Pb value has increased slowly. This increased value is not related with black carbon or bromine. It may come from paints, manufacturing products for Pb acid batteries and foundries etc. Therefore, suspect sources should be investigated and controlled for the management of pb level in the ambient air. Key words: Proton Induced X-Ray Emission, Pb acid batteries, Particulate Matter doi: 10.3329/jbas.v32i2.2427 Journal of Bangladesh Academy of Sciences Vol.32(2) 2008 209-217